PENGGUNAAN MEDIA KONKRIT DALAM PEMBELAJARAN KONSEP BANGUN RUANG UNTUK MENINGKATKAN KETERAMPILAN PEDAGOGIK MAHASISWA CALON GURU SD/MI - Verawati Verawati (NIZHAMIYAH, 2025)
This case study investigates the impact of concrete teaching materials on the development of pedagogical skills among pre-service primary school teachers in teaching three-dimensional geometry. The participants were 24 pre-service teachers enrolled in a mathematics teaching methods course. Data were collected via a pedagogical skills rubric (observation), semi-structured interviews, reflective journals, and microteaching video documentation. Data analysis combined descriptive qualitative methods with simple quantitative comparison of pre- and post-intervention scores. Results show substantial improvement in pedagogical skills after the integration of concrete materials—average scores rose from 62.5 to 80.4 (out of 100). Participants reported greater confidence in teaching and improved ability to translate abstract geometric concepts into accessible, student-centered learning activities. The study recommends embedding hands-on media training in teacher education curricula to strengthen pedagogical content knowledge (PCK) and practical teaching competencies. Keywords: concrete materials, spatial geometry, pedagogical skills.